The Role of the Intestine in the Development of Hyperuricemia - Yin, Hui; Liu, Na; Chen, Jie (Frontiers in Immunology, 2022)
Gout is a common inflammatory arthritis caused by the deposition of sodium urate crystals in the joints. Hyperuricemia is the fundamental factor of gout. The onset of hyperuricemia is related to purine metabolism disorders or uric acid excretion disorders. Current studies have shown that the intestine is an important potential organ for the excretion of uric acid outside the kidneys. The excretion of uric acid of gut is mainly achieved through the action of uric acid transporters and the catabolism of intestinal flora, which plays an important role in the body's uric acid balance. Here we reviewed the effects of intestinal uric acid transporters and intestinal flora on uric acid excretion, and provide new ideas for the treatment of hyperuricemia and gout.